Outcomes of a modified Bresler procedure for the treatment of rectocele with rectal intussusception. (4th July 2020) - Deng, Qun; Yu, Kai-Lin; Liu, Zhi-Yong; Shen, Zhong; Wang, Ya-Hui; Song, Yong-Mao; Wang, Chang-Jian; Xu, Xiao-Ping; Wang, Jian-Wei
Abstract: Background: Obstructed defecation syndrome (ODS) is a condition that is frequently caused by rectocele and rectal intussusception. This study aimed to evaluate the effectiveness of a modified Bresler procedure for the treatment of ODS. The outcomes of this modified procedure were compared with the stapled transanal rectal resection (STARR) procedure. Methods: We performed a retrospective analysis of the clinical data from 76 female patients who presented with ODS between June 2014 and June 2016. The patients were divided into two treatment groups, namely Modified and STARR. Patients in the Modified group ( n = 36) underwent the modified Bresler procedure, which involved posterior rectal-wall resection using a circular tubular stapler with multilevel purse-string sutures. Patients in the STARR group ( n = 40) underwent the standard STARR procedure. We analysed post-operative complications, Wexner constipation scores (WCS), rectocele depths, and four-point post-operative satisfaction scales. Results: Patients in the Modified group exhibited shorter operative times and fewer post-operative complications (both P < 0.05). At 12 months post-operatively, both the Modified and STARR groups displayed a significant improvement in the Wexner constipation score and the depth of rectocele. The post-operative WCS for the Modified group were significantly improved compared to those for the STARR group ( P < 0.05), while there was no significant difference in the rectocele depth between the two groups ( P > 0.05). Post-operative interviews at post-operative 12 months showed that patients in the Modified group had a better satisfaction ( P = 0.05). Conclusions: Our modified procedure may be an effective treatment strategy for patients experiencing ODS caused by rectocele and rectal intussusception, with fewer complications and effective relief of symptoms.